509 Potent and selective inhibition Of AXL receptor tyrosine kinase for the treatment of cancer. (10th December 2020) - Paprcka, Susan; Udyavar, Akshata; Sridhar, Subhasree; Miles, Dillon; Chen, Yu; Cho, Sean; Foley, Corinne; Grange, Rebecca; Leleti, Manmohan; Zhao, Sharon; Jin, Lixia; Young, Stephen; et al.
Abstract : Background: AXL receptor tyrosine kinase (AXL) is a transmembrane protein that is over-expressed in a variety of cancer and immune cells. AXL signaling has been implicated in creating an immunosuppressive tumor microenvironment (TME) through both tumor-intrinsic and immunomodulatory mechanisms 1, 2, 3, 4, 5 promoting resistance to various therapies. 6, 7, 8, 9 Methods: Compound inhibition potency against the kinase activity of AXL and other kinases was determined by detecting phosphorylated substrate using homogeneous time-resolved fluorescence (HTRF). Binding affinity of inhibitor to intracellular AXL kinase was determined by monitoring displacement of a competitive fluorescent tracer using an AXL NanoBRET assay. Recombinant Gas6, cancer cell lines, whole blood or isolated cells from healthy donors were used to determine the reduction in AXL-mediated signaling in-vitro. PK/PD and anti-tumor effects of selected AXL inhibitors were evaluated in murine models. Results: AXL is highly expressed on a subset of immune cells, including DC's, NK cells and M2 macrophages as well as fibroblasts, which contribute to a blunted anti-tumor response. Consistent with these observations, AXL is strongly associated with increased infiltration of macrophages, exhausted NK and T-cells, as well as significantly increased CD73 expression in multiple cancer types in TCGA. Additionally, AXL expression is strongly and significantly correlated with epithelial-mesenchymal transition (EMT), which further generates an immunosuppressive TME and promotes resistance to immune, targeted and chemotherapies. High expression of AXL is also strongly associated with poor survival in NSCLC, pancreatic, breast, head & neck, stomach, colorectal, ovarian & prostate adenocarcinomas, especially in the metastatic setting. AXL inhibitors that exhibit high potency in both biochemical (IC <5nM) and cell-based (IC <25nM) assays in addition to good selectivity against closely related kinases MER and TYRO3 (>90x and >25x fold selectivity, respectively) as well as other kinases involved in downstream signaling such as PI3K have been developed. Initial studies in animal models indicate a favorable pharmacokinetic profile and anti-tumor efficacy. Conclusions: AXL is a promising therapeutic target involving both immunomodulatory and tumor-intrinsic mechanisms. AXL inhibition reduces the immunosuppressive TME, enables activation of an anti-tumor immune response and renders tumors more susceptible to previously resistant therapies. Highly potent and selective AXL inhibitors have been designed, displaying biological profiles superior to those of less-selective molecules currently advancing through clinical development. References: Gjerdrum C, Tiron C, Hoiby T, et al. Axl is an essential epithelial-to-mesenchymal transition-induced regulator of breast cancer metastasis and patient survival. PNAS 2010; 107(3):1124–1129. Ying X, Chen J, Huang X, Huang P, Yan S. Effect of AXL on the epithelial-to-mesenchymal transition in non-small cell lung cancer. Exp Ther Med 2017; 14 :785–790. Tsukita Y, Fujino N, Miyauchi E, et al. Axl Kinase drives immune checkpoint and chemokine signalling pathways in lung adenocarcinomas. Molecular Cancer 2019;18 :24. Terry S, Abdou A, Engelsen AST, et al. AXL targeting overcomes human lung cancer cell resistance to NK- and CTL-Mediated Cytotoxicity. Cancer Immunol Res 2019;7(11):1789–1802. Scutera S, Fraone T, Musso T, et al. Survival and migration of human dendritic cells are regulated by and IFN-alpha-Inducible Axl/Gas6 Pathway. J Immunol 2009; 183 :3004–3013. Wilson C, Ye X, Pham T, et al. AXL Inhibition sensitizes mesenchymal cancer cells to antimitotic drugs. Cancer Res 2014;74(20):5878–5890. Ludwig KF, Du W, Sorrelle NB, et al. Small-Molecule Inhibition of Axl targets tumor immune suppression and enhances chemotherapy in pancreatic cancer. Cancer Res 2018; 78(1):246–255. Brand TM, Iida M, Stein AP, et al. AXL mediates resistance to cetuximab therapy. Cancer Res 2015;74(18):5152–5164. Guo Z, Li Y, Zhang D, Ma J. Axl Inhibition induces the antitumor response which can be further potentiated by PD-1 blockade in the mouse cancer models. Oncotarget 2017; 8(52):89761–89774